Noninvasive method of monitoring the functional state of living cells - T. V. Parkhomenko; O. V. Galibin; V. V. Tomson (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The article is devoted to the generalization of information on the use of potential-sensitive probes (PSP) to assess the viability and functional state of an entire cell. Usage of membrane PSP is of great importance for assessing both the viability and functional integrity of the cells and their structural components (mitochondria, nuclei, cytoplasmic membranes, ion channels). Potential advantage of this approach includes studies of native viable cells in order to assess functional state of donor hematopoietic cells before transplantation as well as upon their storage and cultivation. These staining tools allow to assess the state of cellular bioenergetics, i.e., the balance between production and consumption of energy in living cells. The production of energy in mitochondrial structures ensures the cell viability, whereas its impairment leads to the development of different disorders and aging. In clinical medicine, this method can be used to assess the condition of donor cells before their transplantation, primarily in oncohematology, the treatment of patients with severe ischemic myocardial lesions.The purpose of the work: to study the results of the research of the use of PSP to assess the energy potential and viability of cells.